Endometrial stromal sarcoma of the uterus presenting as pulmonary metastasis. (1st August 2013) - Binesh, Fariba; Taghipour Zahir, Shokouh; Akhavan, Ali; Roshan Bovanlu, Taghi
Abstract : Endometrial stromal sarcoma (ESS) is a rare uterine sarcoma. Compared with other uterine malignancies, it occurs at an earlier age (42–58 years) and about 10–25% of the patients are premenopausal. The tumours have an indolent growth, with a tendency for late recurrence. Metastases are rarely detected before the diagnosis of the primary lesion. We report a case of ESS with pulmonary metastasis as a prodromal manifestation.